Psychological aspects in human trafficking for sexual exploitation: a systematic review (2023)
This article is a systematic review of the crime of trafficking in persons for sexual exploitation, relating the psychological aspects of the victims and the traumas and disorders caused to mental health with the violation of human rights. The methodology followed the Prisma statement, with scientific articles deposited in three databases: Pubmed, Web of Science (WoS), and Springer; Three search equations were crossed with their Booleans under inclusion and exclusion criteria. As a result of the screening, 27 documents were obtained to conclude that the crime of human trafficking qualifies as a crime against humanity given the psychological consequences of the victims and the difficulty of reintegration, but also, the need to generate inter-country actions to confront criminal gangs.